2016
DOI: 10.3892/mco.2016.875
|View full text |Cite
|
Sign up to set email alerts
|

Profiling analysis of circulating microRNA expression in cervical cancer

Abstract: Abstract. MicroRNA (miRNA) expression is altered in cancer cells and is associated with the development and progression of various types of cancer. Accordingly, miRNAs may serve as diagnostic or prognostic biomarkers in cancer patients. In this study, we attempted to analyze circulating exosomal miRNA in patients with cervical cancer. Total RNA was extracted from the serum of healthy subjects, subjects with cervical intraepithelial neoplasia (CIN) and patients with cervical cancer. We first investigated miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…After removing 158 duplicate articles, we included the eligible studies through reading titles and abstracts. Ultimately, ten articles [31,[47][48][49][50][51][52][53][54][55], covering 50 studies, were included according to the inclusion and exclusion criteria. Figure 1 showed the flow diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…After removing 158 duplicate articles, we included the eligible studies through reading titles and abstracts. Ultimately, ten articles [31,[47][48][49][50][51][52][53][54][55], covering 50 studies, were included according to the inclusion and exclusion criteria. Figure 1 showed the flow diagram of study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Imaoka et al [27], using miRNA array analysis, found that a high serum level of miR-1290 was correlated with aggressiveness and poor prognosis in colorectal cancer. Nagamitsu and colleagues [28] reported that circulating miR-1290 was increased in cervical cancer patients compared with healthy controls. Given the variable plasma expressions of miRNA, it would be sensible to combine several miRNAs and other serum biomarkers to comprehensively screen PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…The SCC-Ag is extensively applied clinically as a prognostic and diagnostic biomarker for patients with cervical cancer (7,24). However, this antigen is not significantly increased during the early stages of disease (25). Therefore, it is necessary to identify novel biomarkers for the early detection of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%